BORDERLINE PERSONALITY DISORDER DURING COVID-19 PANDEMIC - Dearisa Surya Yudhantara; Ratri Istiqomah (Journal of Psychiatry Psychology and Behavioral Research, 2021)
Individuals with pre-existing mental problems are more likely to relapse or experience a recurrence of symptoms during The COVID-19 pandemic. This vulnerability can also manifest in those who suffer from Borderline Personality Disorders (BPD). Pandemic conditions significantly restrict people's social interaction for an extended period of time, resulting in severe restrictions on daily living routines and social isolation. When social interaction is restricted, emotional dysregulation and difficulty reading others' emotional expressions may lead borderline patients to anticipate subtle emotional expressions of fear or anxiety in their significant others, eliciting intense reactions such as outbursts of anger, increased irritability, and impulsive behaviors. Patients with personality disorders are more likely to experience crisis during a pandemic, which can result in self-inflicted injury or suicide. Psychotherapeutic interventions to support individuals with BPD who seek secondary mental health care include Dialectical Behavior Therapy (DBT), Mentalization-Based Therapy (MBT), and Schema-Focused Therapy (SFT), in addition to other briefer skills-based group therapy sessions, many of which have been made difficult to obtain since the COVID-19 pandemic began. Dialectical Behavioral Therapy (DBT) is one of the most effective psychotherapies for borderline personality disorder (BPD). With the adoption of social distancing and the elimination of face-to-face activities, there are challenges to DBT. DBT delivered via telemedicine and telehealth are pragmatic alternatives that have had varying degrees of success during this pandemic.